Resistivity correction and water saturation evaluation for calcareous tight sandstone reservoir: A case study of G oil field in Sichuan Basin - Yu, Zhang; Jun, Jia; Hua, Hu; Yao, Du; Hongyi, An; Shi, Fang (Frontiers in Earth Science, 2023)
The calcareous tight sandstone reservoir of the Triassic Shaximiao Formation in the G oil field of the central Sichuan Basin has high calcium content and abnormally high resistivity, making it difficult to reveal the oil-bearing property, evaluate water saturation, and calculate geological reserves. In this work, a petrophysical volume model of calcareous tight sandstone was established through systematic petrophysics experiments and the analysis of the main control factors of oil content. A method of using conventional logging data to calculate the calcium content of the reservoir and correct the calcium content of resistivity was proposed. After resistivity correction, the water saturation of the tight calcareous sandstone reservoir was more accurately calculated based on variable rock-electro parameters. The results indicated that with the decrease in calcium content and the increase in feldspar content, the reconstructive effect of corrosion was enhanced, the physical properties and pore structure of the reservoir were improved, and the oil content increased. The calcium content of the reservoir can be continuously calculated by the volume model and the crossplot of logRtn/ACn and Vca/POR. The resistivity of the reservoir with a high calcium content can be corrected using the resistivity index of calcium content (Ica). In conjunction with the water saturation calculation model using variable parameters, the accuracy of calculated water saturation was 14% and 5.8% higher than the calculation results without resistivity correction and using fixed rock-electro parameters, which can satisfy the requirements for reservoir evaluation and the calculation accuracy of hydrocarbon reserves.